Workshop Pengembangan Perangkat Pembelajaran Kurikulum Merdeka Bagi Mahasiswa Calon Guru Agama Katolik - Berangka, Dedimus; Belang, Bertolomeus; Leba, Videlis Nilo (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
In practical field experiences with an independent curriculum framework, learning tools, become interactive learning media that help teachers practice when teaching and interacting with students. The problem that occurs is that student teachers do not yet properly understand the concept and implementation of the curriculum. The pre-test results show that students do not have sufficient understanding, as evidenced by the average score obtained of 60.9. The improvement solution offered is a workshop on the implementation and preparation of independent curriculum tools in schools. This activity was carried out for 6 days with 120 participants. The implementation method uses a participatory approach with pretest activity steps, material presentation and posttest. The results of this workshop activity show that the workshop activity has a positive impact on students. In terms of the ability to understand the curriculum they are learning and the components in the learning tools, this is proven by the post-test scores with an average score of 82.3, while in terms of the ability to develop learning tools in group work, students can develop teaching modules and Pancasila profile modules correctly. The positive impact of this workshop activity increases students' self-confidence in carrying out practical field experiences at school in educational units according to their phases and characteristics.